Pemanfaatan Debit Air Perusahaan Daerah Air Minum Perumahan Untuk Pembangkit Listrik Tenaga Pico Hidro - Juhana (CV. Multi Kreasi Media, 2023)
Advances in renewable energy sources have led to the development of more powerful power plants using fewer fossil fuels to protect the environment and reduce the amount of greenhouse gases produced. Some of the most common renewable energy sources that have been developed are water, sun, wind and biomass. In this research, an analysis was carried out on how water flow from the regional drinking water company (PDAM) can produce electrical energy. System design, system work and analysis of the effectiveness of the pico hydro type hydroelectric power generation system using household PDAM water discharge. The method is carried out by installing branching pipes, namely the channel leading to the generator and the channel leading to the residence. The author's research objectives are divided into three, namely measuring water discharge at 4 times, namely morning, afternoon, evening and night, calculating voltage, current and electrical power, and determining the battery charge at these 4 times. The results obtained are a water discharge of 7.6 liters/minute with the largest electric current at night being 0.04A, the 5Ah battery charging time is 125 hours, this charging will not continue as long as the use of PDAM water and free electrical energy stored in the battery from a 12V marine generator. It can be concluded that night is the right time to charge the battery.